2013
DOI: 10.1007/s10803-013-1938-0
|View full text |Cite
|
Sign up to set email alerts
|

Using Self- and Parent-Reports to Test the Association Between Peer Victimization and Internalizing Symptoms in Verbally Fluent Adolescents with ASD

Abstract: The current study tested the associations between peer victimization and internalizing symptoms in 54 verbally fluent adolescent males with a diagnosis of autism spectrum disorder. Adolescent- and parent-reports of multiple types of peer victimization and internalizing symptoms were used. First, the validity and reliability of the adolescent-report measure of peer victimization were successfully tested, with some exceptions. Then, structural equation models showed that adolescent-reports of peer victimization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 32 publications
8
59
1
Order By: Relevance
“…However, our findings may also support the possibility that childhood adversity contributes to the high rate of mental health issues experienced by individuals with ASD (Kerns et al, 2015b; Adams et al, 2014). Shared genetic/biological pathways likely contribute to psychiatric comorbidity in ASD (White et al, 2014), yet ACEs may also play an important role as known contributors to emotional dysregulation (a potential precipitant of psychiatric co-occurrence in ASD; White et al, 2014; Mazefsky et al 2013) and psychiatric symptoms (Edwards et al, 2003).…”
Section: Discussionsupporting
confidence: 57%
“…However, our findings may also support the possibility that childhood adversity contributes to the high rate of mental health issues experienced by individuals with ASD (Kerns et al, 2015b; Adams et al, 2014). Shared genetic/biological pathways likely contribute to psychiatric comorbidity in ASD (White et al, 2014), yet ACEs may also play an important role as known contributors to emotional dysregulation (a potential precipitant of psychiatric co-occurrence in ASD; White et al, 2014; Mazefsky et al 2013) and psychiatric symptoms (Edwards et al, 2003).…”
Section: Discussionsupporting
confidence: 57%
“…This is one possible mechanism through which SC difficulties may predispose to greater SA symptoms in childhood; however, there may be several alternative mechanisms, for example peer victimization, bullying, or social insight, 35 that may contribute to the development of SA in those who exhibit severe SC difficulties. For example, in adolescents with ASD, self-reported peer victimization and bullying are associated with increased internalizing problems 36 . It is possible that SC difficulties predispose to these additional risk factors or that they develop independent of social ability.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that total levels of peer victimization were strongly related to symptoms of panic and moderately related to symptoms of depression. Adams et al (2013) found that adolescent reports of peer victimization were associated with internalizing symptoms. The authors also found that parental report of peer victimization was not associated with internalizing symptoms.…”
Section: Overviewmentioning
confidence: 99%
“…The authors also found that parental report of peer victimization was not associated with internalizing symptoms. Adams et al (2013) commented that the experience of peer victimization may help to explain the high rates of internalizing behaviors in adolescents with ASD. Rosbrook and Whittingham (2010) found social problem-solving ability and past teasing experiences to be significant mediators between traits of autism and anxiety symptoms.…”
Section: Overviewmentioning
confidence: 99%